Ambiente interactivo para la visualización de conceptos asociados a las técnicas de diseño de algoritmos (2016)
This book presents a playful, graphic, and interactive alternative for learning techniques associated with algorithm design, based on a set of predefined situations, with algorithms taught frequently to students, which will allow them to develop comparisons, workshops, and academic assignments, thus helping to support traditional teaching methodologies, making better use of the available technological learning tools, to stimulate their easy learning and application.